The Reality of Applying Administrative Transparency in King Abdulaziz University from the Perspective of Department Heads and Female Supervisors - Alshehri, Asma Ali Hamdan; Alsaigh, Najat Mohammed Saeed (Journal of Educational and Psychological Sciences, 2023)
The research aimed at recognizing the reality of administrative transparency at King Abdulaziz University according to the perspective of department heads and female supervisors. To accomplish this aim, the research adopted the descriptive approach and used a questionnaire as a tool of data gathering which was administered to a random sample comprising (53) department heads and female supervisors. The research concluded many findings such as: The reality of applying administrative transparency at King Abdulaziz University according to the perspective of department heads and female supervisors was at a (high) degree, with a general average = (3.56), the absence of any statistically significant differences among the mean rankings of the sample individuals that were affected by gender variable, the existence of differences among the mean rankings of the sample individuals in the field of (information systems) that were affected by the years of experience variable, in favor of (those having more than ten years of experience), and the fact that the field of administrative communication was the most applied transparent field with an average = (3.78), followed by the information systems field (average = 3.69), then the work procedures field (average = 3.59), and finally, the administrative accountability field (average = 3.23). The research concluded many recommendations, the most prominent of which were: that the Ministry of Education has to form an obligatory transparency framework at universities, activate leaders' training programs concerning transparency and accountability, establish a specialized unit for monitoring transparency-connected systems at university, increase the effectiveness of accountability through enhancing the accountability culture at all levels of jobs hierarchy, fight corruption in all forms, and attempt to adapt work procedures by limiting contradiction between tasks and responsibilities in order to ensure efforts integration.
Keywords: Administrative transparency; King Abdulaziz University